COLLABORATIVE STRATEGIES IN INNOVATION: CALCULATING STRATEGIC DIVIDEND AND TRANSACTIONAL EFFICIENCY FOR ORGANIZATIONAL GROWTH - Aripin, Zaenal; Yuliaty, Farida; Haryaman, Adang (KRIEZ ACADEMY : Journal of development and community service, 2024)
Collaborative strategies in innovation play an important role in accelerating organizational growth and sustainability in a global era full of challenges. This research discusses the importance of taking into account both strategic dividends and transactional efficiency in optimizing innovative collaboration for long-term organizational growth. Factors such as clarity of goals and expectations, trust and openness, open communication, effective risk management, and utilization of advanced information technology play a key role in improving transactional efficiency in innovative collaborations. Increasing transactional efficiency in innovative collaborations also has a positive impact on the long-term growth of organizations, by expanding market coverage, increasing competitiveness and brand image, creating sustainable growth and competitive advantage, as well as maintaining the sustainability of partnership relationships and strengthening networks. Therefore, organizations need to actively consider both strategic dividends and transactional efficiencies in the planning and implementation of their innovative collaborations, and continuously refine and adapt their strategies according to changing needs and challenges. In this way, organizations can maximize the added value potential of their partnerships and achieve sustainable long-term growth.